Jump kinetics, bone health and nutrition in elite adolescent female athletes - Moresi, M.; Bradshaw, E.; Greene, D.; Naughton, G. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
The relationship between physical force capacity (kinetics), nutritional intake, and lower limb bone health was the focus of the present study. 119 adolescent female athletes across four sub-populations, gymnastics, track and field, water polo and non-active controls, completed a series of jump tasks, bone scans, and a three day food diary. Statistical analysis using two-way analysis of variance was used to compare key measures between groups. Significant differences were identified for bone and jump parameters. Stepwise linear regression analysis identified jump kinetics as best able to predict distal tibial trabecular bone density (r2 = 44.2%, p = 0.000) and bone strength (r2= 28.5%, p = 0.000). Athletes engaging in weight-bearing loading appear advantaged in site-specific markers of bone health.